PENGARUH PENGEMBANGAN KARIR DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA BALAI BESAR METEOROLOGI KLIMATOLOGI DAN GEOFISIKA WILAYAH II TANGERANG SELATAN - Susanti, Fahmi; Alif, Rizki Nur (Journal of Research and Publication Innovation, 2024)
This study aims to find out whether there is an influence of career development and motivation on employee performance at the Center for Meteorology, Climatology and Geophysics Region II South Tangerang. To find out whether the influence of career development on employee performance at the Center for Meteorology, Climatology and Geophysics Region II South Tangerang is the highest, to find out if there is an influence of motivation on employee performance at the Center for Meteorology, Climatology and Geophysics Region II South Tangerang. This research method uses an associative method with a quantitative descriptive technique, meaning to find out the relationship between two or more variables. The sampling technique used in probability sampling uses the saturated sampling technique method. The data collection technique in this study uses observation and questionnaire techniques. The data obtained by the questionnaire with the number of respondents was 80 employees. Linear regression test method, correlation coefficient test, determination coefficient test and hypothesis test. The results of this study show that career development has a significant effect on employee performance with the regression equation Y = 22.421 + 0.421X1, the correlation coefficient value is 0.452, meaning that both variables have a moderate level of relationship with a determination coefficient of 20.4%. The hypothesis test was obtained by calculating t > t table or (4,471>1,665). Thus H0 : p1 = 0 is rejected and Ha : p1 ≠ 0 is accepted, meaning that there is a significant influence between career development and employee performance. Motivation had a significant effect on employee performance with the regression equation Y = 19.786 + 0.491X2, the correlation coefficient value was 0.496, meaning that both variables had a moderate level of relationship with the determination coefficient of 24.6%. The hypothesis test was obtained by calculating t > t table or (5,040 > 1,665). Thus H0 : p2 = 0 is rejected and Ha : p2 ≠ accepted, meaning that there is a significant influence between motivation and employee performance. Career development and motivation have a significant effect on employee performance with the regression equation Y= 15.025 + 0.255X1 + 0.357X2. The value of the correlation coefficient was obtained as 0.549, meaning that the independent variable with the bound variable had a moderate level of relationship with the determination coefficient or simultaneous influence of 30.2% while the remaining 69.8% was influenced by other factors. The hypothesis test obtained the F value calculated > F table or (16.647 > 3.115). Thus H0 : p3 = 0 was rejected and Ha : p3 ≠ 0 was accepted, meaning that there was a significant simultaneous influence between career development and motivation on employee performance at the Center for Meteorology, Climatology and Geophysics Region II of South Tangerang.